Dukungan Keluarga Dalam Penatalaksanaan Hipertensi di Puskesmas Candirejo Magetan - Yunita Ayu Rahmawati; Kartinah Kartinah (Universitas Muhammadiyah Surakarta, 2017)
Family support in hypertensive patients during treatment if not well then the role of family maintenance is not good. Support family members in treatment will help to determine the success of the implementation of such treatments. support is not limited to family members on financial matters, but also on the willingness of family members to accompany patients when needed. By using this type of qualitative research with the phenomenological approach to research was conducted in hypertensive patients at the health center Candirejo Magetan in December 2012 to see family support in the management of hypertension in the Health Center Candirejo Magetan. From these studies can be from six informants who have emotional support, instrumental support and the support of good information, such as meeting all the needs of informants, give love, to finance treatment and provide information about the treatment of hypertension to the informant. While the appreciation of the support of all informants has gotten positive support.